KONSEP HARGA DAN MEKANISME PASARDALAM PERSPEKTIF IBNU TAIMIYAH - Kahfi, Ashhabul; Hasanudin; Helmi Saftarijan (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2026)
This study examines the concept of price and market mechanism in the thought of Ibn Taymiyyah and evaluates its relevance to contemporary issues in Islamic economics. The research adopts a qualitative library-based method using a descriptive-analytical approach within a historical-contextual framework. Primary sources consist of Ibn Taymiyyah’s major works, while secondary sources are drawn from recent scholarly literature addressing fair pricing, market mechanisms, state intervention, monopoly, hoarding, and transaction ethics. The findings indicate that, according to Ibn Taymiyyah, prices are fundamentally formed through the natural interaction of supply and demand; therefore, price fluctuations should not automatically be regarded as a form of injustice. Nevertheless, market mechanisms must operate within a moral framework grounded in honesty, transparency, justice, and the prohibition of manipulation. The state is not justified in imposing prices arbitrarily, yet it retains legitimate authority to intervene when market distortions occur, such as monopoly, hoarding, fraud, and market domination that undermine public welfare. In this regard, Ibn Taymiyyah’s thought reflects a synthesis of market freedom, the ethics of muamalah, and state supervision aimed at promoting economic justice and the public good.